SIMULASI GERAK JATUH BEBAS MENGGUNAKAN PYTHON - br Sembiring, Naila Davina; Satria, Bima Putra; Ulfa, Maria; Nasution, Adelyna Oktavia (Bahasa Indonesia, 2025)
A free fall motion simulation based on Python was developed as an interactive and visual physics learning tool. The project integrates the Pygame library for animation and Matplotlib for graphical representation, illustrating the motion of an object falling from a certain height due to gravitational acceleration. The development process includes needs analysis, design, program implementation, and evaluation of its effectiveness in enhancing students' understanding of physics concepts. The simulation output shows a downward-opening parabolic graph, consistent with the laws of uniformly accelerated linear motion (GLBB). This tool provides a concrete visualization of the relationship between time, velocity, and position, making it an effective aid in learning the concept of free fall motion.